MENINGKATKAN HASIL BELAJAR PKN MATERI MENGENAL SIMBOL PANCASILA KELAS I SD NEGERI 030 SIABU KAB. MANDAILING NATAL - Siregar, Sulis Hariati; Samakmur, Samakmur; Nurbaiti, Nurbaiti; Safitri, Reviva; Dongoran, Rahmad Afandi (Jurnal Ilmiah Pendidikan Dasar (JIPDAS), 2024)
Study aims to describe the data and analyze the implementation the use of the Picture And Picture Model to improve science learning outcomes material get to know the human skeleton class l SD Negeri 030 Siabu |Natal Regency Middle. This type of research is classroom action research (CAR), subject in This study included all fifth grade students at SD Negeri 030 siabu  District Central Tapanuli which totaled 20 0people consisting of 14 women and men 6 men. The instruments used were teacher, student, and observation sheets sheet test. The results of this research show that through the Picture And Picture Model can improve the learning outcomes of fifth grade students at SD Negeri 030 siabu   Central Tapanuli Regency student learning outcomes have increased from cycle I to II, it is hoped that the Picture And Picture Model will increase student learning outcomes and included in the good category. It is also shown that there is an increase in each cycle through the teacher's observation sheet improvement in the Indonesian cycle, a total score of 72 was obtained with a percentage value of 72% included in the high category and student observation sheets at the Indonesian cycle obtained a total score of 43 with a percentage value of 76.78% including good category. While cycle II obtained a total score of 52 with a percentage value of 92.78% included in the very good category. Next, look at the test sheet if compared to the Indonesian cycle and cycle I1. In the Indonesian cycle, the number is obtained average value of 72.92 2% increase with a total average value of 86.669% included in the category tall. Through the Picture And Picture Model, it can improve student learning outcomes forgetting the material Get to know the human skeleton Class l SD Negeri 030 Siabu Mandailing Natal.   Keywords: Picture And Picture learning model and the results of learning to know humans   Abstrak Penelitian ini bertujuan untuk mendeskripsikan data dan menganalisis pelaksanaan penggunaan Model Picture And Picture untuk meningkatkan hasil belajar PKN materi mengenal Simbol pancasila  kelas l  SD Negeri 030 Siabu   Kabupaten Mandailing Natal . jenis penelitian ini merupakan penelitian tindakan kelas (PTK). Subjek dalam penelitian ini adalah seluruh siswa kelas l SD Negeri 030 Siabu  Kabupaten Mandailing Natal  yang berjumlah sebanyak 20 0rang yang terdiri dari 14 perempuan dan laki-laki 6 orang. Adapun instrumen yang digunakan adalah lembar observasi guru, siswa, dan tes lembar soal. Hasil penelitian ini menunjukkan bahwa melalui Model Picture And Picture dapat meningkatkan hasil belajar siswa kelas l SD Negeri 030 Siabu  Kabupaten Mandailing Natal  hasil belajar siswa mengalami peningkatan dari siklus I ke II, dengan diharapkannya Model Picture And Picture hasil belajar siswa meningkatkan dan termasuk dalam kategori baik. Hal ini juga ditunjukkan adanya peningkatan tiap siklus melalui lembar observasi guru peningkatan pada siklus Indonesia diperoleh jumlah skor 72 dengan nilai prensentase 72% termasuk dalam kategori tinggi dan lembar observasi siswa di siklus Indonesia diperoleeh jumlah skor 43 dengan nilai presentase 76,78% termasuk kategori baik. Sedangkan siklus II diperoleh jumlah skor 52 dengan nilai prensentase 92,78% termasuk kategori sangat baik. Selanjutnya dilihat pada lembar soal tes apabila dibandingkan dengan siklus Indonesia dan siklus II. Pada siklus Indonesia didapatkan jumlah nilai rata 72,92% peningkatan dengan jumlah nilai rata-rata 86,66% termasuk dalam kategori tinggi. Melalui Model Picture And Picture dapat meningkatkan hasil belajar siswa pkn materi mengenal Simbol pancasila  Kelas l SD Negeri 030   Kabupaten Mandailingi Natal. Kata Kunci:  Model pembelajaran Picture and Picture, hasil belajar, Simbol pancasila